Desenvolvimento de um manual de orientações para o cuidador do paciente acamado no atendimento domiciliar - Alécio, Renata (2024)
The focusofthisstudy lies in thedevelopmentof a manual aimedatguidingthecareprovidedtobedriddenpatients in thecontextof home care. The overall objectiveistocreate a comprehensiveguidetailoredtocaregiversofbedriddenpatients. The methodisbasedonanintegrativeliterature review. The resultshighlightthatthe use ofguidesandmanuals emerges as a crucial facilitator in thecareprocess for bedriddenpatients, playing a pivotal role in empoweringcaregivers for theproperexecutionofnecessary procedures. It isconcluded, therefore, thatcaregiver training isessentialnotonlytoensureeffectivecare for bedriddenpatientsbutalsoto minimize risksandpotentialcomplicationsthatmayarise in the home environment.